2013
DOI: 10.3109/00016357.2013.824606
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic intervention combined with myofunctional therapy increases electromyographic activity of masticatory muscles in patients with skeletal unilateral posterior crossbite

Abstract: Orthodontic intervention combined with myofunctional therapy in patients with skeletal unilateral posterior crossbite provided an increase in the electromyographic activity of the masseter and temporalis muscles during mandibular rest and habitual mastication, with predominantly bilateral mastication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 8 publications
0
11
0
6
Order By: Relevance
“…On the other hand, one study did not find any significant difference of the functional asymmetry in masseter and temporalis muscle activity immediately after cross-bite treatment (25). sEMG measurements during clenching were carried out by all four studies (7,11,24,25) with similar results reported. Following cross-bite treatment, the masseter and temporalis muscles in the cross-bite side showed a normalisation of the initial asymmetric muscle activity.…”
Section: Results Of Individual Studiesmentioning
confidence: 58%
See 4 more Smart Citations
“…On the other hand, one study did not find any significant difference of the functional asymmetry in masseter and temporalis muscle activity immediately after cross-bite treatment (25). sEMG measurements during clenching were carried out by all four studies (7,11,24,25) with similar results reported. Following cross-bite treatment, the masseter and temporalis muscles in the cross-bite side showed a normalisation of the initial asymmetric muscle activity.…”
Section: Results Of Individual Studiesmentioning
confidence: 58%
“…The asymmetric activity of the masseter and temporalis muscles in three of the studies was normalised following treatment (7,11,24). Nevertheless, one study (25) showed a normalisation only of masseter muscle and no significant changes with regard to the temporalis muscle. sEMG measurements were recorded during mastication in three of the four included articles.…”
Section: Results Of Individual Studiesmentioning
confidence: 80%
See 3 more Smart Citations